Effect of extraction and concentration processes on properties of longan syrup - Surin,S. (Springer India, 2015)
© 2014, Association of Food Scientists & Technologists (India). Longan (Dimocarpus longan Lour.) syrup is a novel liquid sweetener produced from longan, one of the traditional and economic fruits in the Northern of Thailand. In this research, the effect of extraction and concentration processes on properties of longan syrup was investigated. There were two extraction methods (juice extractor and hydraulic press) and three concentration methods (direct heating, steam heating and vacuum evaporation). Results overall showed that the extraction method had no significant (p ≥ 0.05) effect on longan syrup properties, while concentration resulted in the quality changes of longan syrup. Concentration using direct heating of longan juice caused reduction of sucrose content, and longan syrup dark in color. The headspace volatile compounds of longan syrup were sampled using direct headspace technique and further characterized using gas chromatography-mass spectrometry. The identified volatile compounds could be divided into two groups of aroma characteristics which were (1) floral aroma: 3-methybutyl acetate, (β)-ocimene and 2-phenylethyl alcohol and (2) caramel aroma: butyraldehyde, furfural and benzaldehyde. 2-Phenylethyl alcohol, contributing to floral odor, was retained using vacuum evaporation as a concentration method. Result revealed that the optimal concentration process for longan syrup production was vacuum evaporation, providing the highest floral volatile and lowest caramel volatile. Sensory tests confirmed that longan flavor of the syrup produced from the vacuum evaporation process had significantly higher hedonic scores than other processes.